2018
DOI: 10.1111/joa.12821
|View full text |Cite
|
Sign up to set email alerts
|

Pbx loss in cranial neural crest, unlike in epithelium, results in cleft palate only and a broader midface

Abstract: Orofacial clefting represents the most common craniofacial birth defect. Cleft lip with or without cleft palate (CL/P) is genetically distinct from cleft palate only (CPO). Numerous transcription factors (TFs) regulate normal development of the midface, comprising the premaxilla, maxilla and palatine bones, through control of basic cellular behaviors. Within the Pbx family of genes encoding Three Amino‐acid Loop Extension (TALE) homeodomain‐containing TFs, we previously established that in the mouse, Pbx1 play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 84 publications
0
37
0
1
Order By: Relevance
“…As demonstrated by loss of function (LOF) in mice, different Pbx genes play fundamental and pleiotropic roles in organogenesis. Pbx1 homozygous mutant embryos (Pbx1 −/− ) die in utero with dramatic abnormalities in multiple organs DiMartino et al 2001;Kim et al 2002;Manley et al 2004;Brendolan et al 2005;Capellini et al 2006Capellini et al , 2008Capellini et al , 2010Capellini et al , 2011aStankunas et al 2008;Ferretti et al 2011;Vitobello et al 2011;Koss et al 2012;Hurtado et al 2015;Grebbin et al 2016;Villaescusa et al 2016;Losa et al 2018;McCulley et al 2018;Welsh et al 2018). In contrast, Pbx2 −/− mice do not display detectable abnormalities , while Pbx3 −/− mutants die perinatally, from central respiratory failure ).…”
Section: Control Of Embryonic Development and Onset Of Disease Undermentioning
confidence: 99%
See 2 more Smart Citations
“…As demonstrated by loss of function (LOF) in mice, different Pbx genes play fundamental and pleiotropic roles in organogenesis. Pbx1 homozygous mutant embryos (Pbx1 −/− ) die in utero with dramatic abnormalities in multiple organs DiMartino et al 2001;Kim et al 2002;Manley et al 2004;Brendolan et al 2005;Capellini et al 2006Capellini et al , 2008Capellini et al , 2010Capellini et al , 2011aStankunas et al 2008;Ferretti et al 2011;Vitobello et al 2011;Koss et al 2012;Hurtado et al 2015;Grebbin et al 2016;Villaescusa et al 2016;Losa et al 2018;McCulley et al 2018;Welsh et al 2018). In contrast, Pbx2 −/− mice do not display detectable abnormalities , while Pbx3 −/− mutants die perinatally, from central respiratory failure ).…”
Section: Control Of Embryonic Development and Onset Of Disease Undermentioning
confidence: 99%
“…There is a strong association between dysregulation of PBX-directed gene networks identified in Pbx LOF mice and human congenital defects, including cleft lip/palate (CL/P) Losa et al 2018;Welsh et al 2018), congenital asplenia (Koss et al 2012), and diabetes (Kim et al 2002;Muharram et al 2005). De novo deleterious sequence variants of PBX1 were discovered recently in children affected by a new syndrome characterized by pleiotropic developmental defects that mimick the phenotypes of Pbx1 −/− embryos.…”
Section: Control Of Embryonic Development and Onset Of Disease Undermentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the redundancy of, and early requirements for, Pbx proteins in mouse embryogenesis (reviewed in Selleri et al 2019), we needed to make use of conditional loss-offunction in Myf5 Cre/+ ;Pbx1 fl/fl ;Pbx2 -/compound mutants. A similar approach, using different conditional Cre lines, has previously been taken to study Pbx functions in craniofacial, spleen, and spinal cord motor neuron development and in adult neurogenesis (Ferretti et al, 2011;Grebbin et al, 2016;Hanley et al, 2016;Koss et al, 2012;Losa et al, 2018;Welsh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Anastasiadi and Piferrer [83] showed that the domestication process in D. labrax resulted notably in genome-wide methylation differences for genes involved in the nervous system and neural crest cell differentiation. In our study, GLI2 [174], PBX1 [175], DLG1 [176] and FOXJ3 [177] are DMC-related genes involved in neural crest cell proliferation and differentiation. ROBO3 is involved in the immune response, but also implied in early neurogenesis [178], as well as NPAS3 [179].…”
Section: Family Effect Development and Few Individualsmentioning
confidence: 95%